If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4y + -1) = 30 Reorder the terms: 2(-1 + 4y) = 30 (-1 * 2 + 4y * 2) = 30 (-2 + 8y) = 30 Solving -2 + 8y = 30 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 8y = 30 + 2 Combine like terms: -2 + 2 = 0 0 + 8y = 30 + 2 8y = 30 + 2 Combine like terms: 30 + 2 = 32 8y = 32 Divide each side by '8'. y = 4 Simplifying y = 4
| 4=6-2s | | -3(y-9)-10= | | 19=2j+3 | | 3(6x-4)=20+2x | | 2u+5=13 | | -4y(2-6)+8y= | | 2(8-3x)=4x-9 | | 2d-11=3 | | -3(x-7)-18= | | 10log(x/10^-12)=150 | | -3(x-6)+12= | | 14-3g=8 | | 72=(2x+4)*9 | | 5n^2=2n | | 5(c+4c)= | | n+0=6 | | y^2-4y+12x-8=0 | | 3s-3=3 | | 2(8-3)=4x-9 | | 10=12-2f | | -3(6-2x)=4(8+4) | | 2y-6+xy-3x= | | -3(6-2x)=4(8+5) | | 4z+10=18 | | ln(2x-99)=0 | | (x-y)x/y=y/x-y(x-y) | | 3.14(5)2(8)= | | X+SqrtX+3=3 | | 8cos(3x)-4*(sqrt(3))=0 | | 17-x/-2=10 | | 17-x/=10 | | ysquared+y=20 |